A prospective cohort study evaluating a novel colonoscopy platform featuring full-spectrum endoscopy - Gralnek, Ian Mark; Segol, Ori; Suissa, Alain; Siersema, Peter D.; Carr-Locke, David L.; Halpern, Zamir; Santo, Erwin; Domanov, Svetlana (Endoscopy, 2013)
Background and study aims: Although colonoscopy is the criterion standard for detecting colorectal adenomas and cancers, a significant percentage of adenomas are missed with this technique. We aimed to establish the feasibility, usability, and safety of a novel colonoscopy platform featuring full-spectrum endoscopy (FUSE).Patients and methods: This was a prospective, single-center pilot and feasibility study. In total, 50 individuals, ages 18 – 70 years, underwent colonoscopy featuring FUSE (up to 330° field of view) for colorectal cancer screening, polyp surveillance, or diagnostic evaluation. Study end points included success of cecal intubation, time to cecal intubation, withdrawal time, total procedure time, success of therapeutic interventions, adverse events, and endoscopists’ subjective evaluation of FUSE.Results: Cecal intubation was achieved in 50/50 individuals (100 %). Time to cecum (minutes, mean ± SD) was 3.1 ± 1.5 minutes, withdrawal time 12.7 ± 4.4 minutes, and total procedure time 15.3 ± 4.6 minutes. In 22/50 cases (44 %), 26 therapeutic interventions were performed: 19 (73.1 %) biopsies and 7 (26.9 %) polypectomies. No acute or delayed adverse events were observed. Patient satisfaction and endoscopist subjective evaluation were high.Conclusions: A colonoscopy platform featuring full-spectrum endoscopy appears feasible, usable, and safe. These results represent an important advance in colonoscopy imaging technology and should be further pursued in comparative human studies.